Single or multiple treatments with lusutrombopag in subjects with thrombocytopenia and chronic liver disease needing an invasive procedure - Davide Scalabrini; Paolo Sciuto; Cristina Felicani; Antonia Rudilosso; Pietro Andreone (Exploration of Drug Science)
Thrombocytopenia is one of the most frequent implications of liver cirrhosis. This condition, when present in the severe form [platelet count (PLT) less than 50 × 109/L] correlates, with an increased risk of bleeding during the main diagnostic-therapeutic procedures which cirrhotic patients usually undergone. In these cases, generally, an infusion of platelets is performed, albeit in recent years has been replaced by a cycle of second generation thrombopoietin receptor (TpoR) agonists. This article reports two different cases concerning respectively an 83-year-old female patient suffering from arterial hypertension, aneurysm of the sub-renal aorta, hepatitis C virus (HCV)-positive liver cirrhosis responsive to treatment with antiviral drugs, and a 2.0 cm diameter hepatocellular carcinoma (HCC) nodule localized in the hepatic segment III and a 53-year-old female patient with HCV-positive liver cirrhosis complicated by portal hypertension with splenomegaly, thrombocytopenia, and F3 esophageal varices at high risk of bleeding. Both of them, eligible for invasive procedures such as HCC transarterial chemoembolization (TACE) and for esophageal variceal band ligation, were prescribed prophylaxis with TpoR agonists due to their severe and persistent thrombocytopenia. These two cases show how a short course of lusutrombopag allows to safely perform one or more invasive procedures and how the administration of the drug can be repeated without losing efficacy. Furthermore, this drug shows an excellent safety profile and avoids the risks of platelet transfusion. In conclusion, second generation TpoR agonists can be considered the prophylactic treatment of choice to reduce the risk of bleeding in patients with liver cirrhosis and severe thrombocytopenia.